2015
DOI: 10.1134/s1068162015040056
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and mutagenic properties of synthetic betulinic acid and betulonic acid

Abstract: Synthesis of betulinic acid was performed from the birch bark extract (Betula pendula). Betulonic acid was intermediate of the synthesis. Both acids were isolated with purity 95%. Genotoxicity and mutagenicity of obtained compounds were analyzed by Ames test and SOS chromotest, none of these properties have been detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Similar to our findings, Frolova et al. [48], demonstrated the absence of mutagenic and genotoxic activity of BA in the Ames test and SOS chromotest. A lack of genotoxicity of BA, a triterpenoid, has also been reported in normal human lymphocyte and fibroblast cells [19, 49, 50].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, Frolova et al. [48], demonstrated the absence of mutagenic and genotoxic activity of BA in the Ames test and SOS chromotest. A lack of genotoxicity of BA, a triterpenoid, has also been reported in normal human lymphocyte and fibroblast cells [19, 49, 50].…”
Section: Discussionsupporting
confidence: 93%
“…According to Rundell et al (2003) , genotoxic damage is likely to undergo repair, whereas mutagenic damage is not, with changes becoming fixed in the genetic material as mutations. Such occurrence is not uncommon in preclinical chemoprevention experiments, both with natural products ( Synder and Gillies, 2002 ; Cunha et al , 2005 ; Rodeiro et al , 2006 ; Hoshina et al , 2013 ; Mendanha da Cunha et al , 2013 ; Luo et al , 2015 ) and with synthetic compounds ( Zhan et al , 2008 ; Cao et al , 2015 ; Frolova et al , 2015 ; de Araújo et al , 2017 ). Although there are significant differences in the frequency of micronuclei between the negative control group and the groups treated with IR-01, Vaz et al (2016) describes that this isolated fact does not necessarily imply in toxicogenetic damage.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro anthelmintic testing of UA and BA on Hymenolepis diminuta (Cestoda) has also revealed that both the compounds possess significant & Arun K. Yadav akynehu@hotmail.com anthelmintic effects (Vijaya and Yadav 2016). The genotoxic testing of BA, using Ames and SOS chromotests, did not revealed any genotoxic or mutagenic effects (Frolova et al 2015). Further, Mullauer et al (2010) have also reported a complete absence of systemic toxicity by BA treatment in rodents up to a dose of 500 mg/kg.…”
Section: Introductionmentioning
confidence: 99%